MITIGASI BENCANA: Manajemen Wabah COVID-19 Di Satuan PAUD - Yudiawan, Agus (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The research encourages the explanation of the mitigation education model and complete disaster mitigation planning in early childhood education schools (PAUD). This research uses library research methods. Data is collected from books, research reports, journal articles, web (internet) relevant to the study of Disaster Mitigation in Schools. Next, the data were analyzed using the content analysis method (content analysis). The results showed that the COVID-19 outbreak disaster mitigation education for PAUD children was one of the reasons children were the most vulnerable during a disaster. Its function is to increase awareness, knowledge, attitudes, skills, and participation in emerging pandemics. The stages of COVID-19 outbreak disaster mitigation in schools include 3 essential preparations. First, prepared, published (1) (2) the existence of school policies, approvals, and regulations. Second, planning, loading; (1) assesses risks, hazards, evaluates and resources; (2) reducing risk; (3) skills in responding and providing disaster relief equipment; (4) education continuity plan. Third, continuous support, updated (1) monitoring; and (2) updating. Mitigation of disasters to be executed is essential as an effort to prepare school resources to cope with disasters.